Modeling Competing Risks in Leukemia Patients: A Survival using the Cause-Specific Hazard Approach - Mohamat Fatekurohman; Ilma Safitri (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
Leukemia is a hematological malignancy with high mortality, where deaths may arise from leukemia or other causes, leading to competing risks. This study aims to model event-specific mortality by integrating the Extended Cox model with time-dependent covariates into the Cause-Specific Hazard (CSH) framework. Secondary data from 130 leukemia patients at RSUD dr. H. Koesnadi Bondowoso (2022–2024) were analyzed, with survival time as the response and two competing events. Parameter estimation was conducted using maximum partial likelihood within a competing risks structure, optimized via Newton–Raphson iteration. The results show that chronic disease significantly increases the hazard of leukemia-related death (HR = 4.60; 95% CI: 1,46-14,44), while sex (HR = 0.30; 95% CI: 0,12-0,73) and body mass index (HR = 0.82; 95% CI: 0,73-0,91) significantly influence mortality due to other causes. These findings demonstrate that the CSH framework provides more accurate and clinically interpretable estimates by distinguishing event-specific risks. This approach supports improved risk stratification and evidence-based clinical decision-making in leukemia management.